1913 Wash. Sess. Laws 90-91, ch. 33, § 1. - (:unkn) unknown (My University, 1913)
Every person who shall use any sink box or sink boat or sneak boat for the purpose of shooting wild ducks, geese, swan or other water fowl, or who shall use any battery, swivel or pivot gun, or any gun other than one to be held in the hands and fired from the shoulder, at any time, for the purposes of shooting wild ducks, geese, swan, brant or other water fowl . . . shall be guilty of a misdemeanor, and upon conviction thereof shall be punished as hereinafter provided.
Keywords: HUNTING REGULATION